2021
DOI: 10.3390/cells10081924
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Models Rediscovered with Super-Resolution Microscopy

Abstract: With the advent of super-resolution microscopy, we gained a powerful toolbox to bridge the gap between the cellular- and molecular-level analysis of living organisms. Although nanoscopy is broadly applicable, classical model organisms, such as fruit flies, worms and mice, remained the leading subjects because combining the strength of sophisticated genetics, biochemistry and electrophysiology with the unparalleled resolution provided by super-resolution imaging appears as one of the most efficient approaches t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…Over the past decade, nanoscopy became a powerful tool to reveal the molecular organization of various types of subcellular structures, such as the nuclear pore complex, centrosomes and synaptic active zones [ 45 , 46 ]. Beyond these, we have successfully used a dSTORM-based pipeline to generate a protein localization atlas at the nanoscale level for about 30 muscle proteins, and to provide a refined molecular model of the sarcomeric I-band and H-zone of the adult Drosophila IFM [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, nanoscopy became a powerful tool to reveal the molecular organization of various types of subcellular structures, such as the nuclear pore complex, centrosomes and synaptic active zones [ 45 , 46 ]. Beyond these, we have successfully used a dSTORM-based pipeline to generate a protein localization atlas at the nanoscale level for about 30 muscle proteins, and to provide a refined molecular model of the sarcomeric I-band and H-zone of the adult Drosophila IFM [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, filamin is observed to accumulate at myofibril microlesions that occur during intense muscle contractions induced by either forced exercise or electrical stimulation [ 10 , 12 , 19 ]. Utilizing single-molecule localization microscopy, it has been revealed that filamin’s actin-binding domains are centrally located within the Z-disc, while the dimerization domains are positioned at the periphery of the disc [ 23 , 42 ], providing an ideal arrangement for sensing Z-disc deformation caused by muscle contractions [ 22 ]. All these experimental data have led to the hypothesis that filamin senses mechanical damage at the Z-disc where it coordinates a compensatory stabilization mechanism that prevents the Z-disc from rupturing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, filamin is observed to accumulate at myofibril microlesions that occur during intense muscle contractions induced by either forced exercise or electrical stimulation [9][10][15]. Utilizing single-molecule localization microscopy, it has been revealed that filamin’s actin-binding domains are centrally located within the Z-disc, while the dimerization domains are positioned at the periphery of the disc [19,38], providing an ideal arrangement for sensing Z-disc deformation caused by muscle contractions [18]. All these experimental data have led to the hypothesis that filamin senses mechanical damage at the Z-disc where it coordinates myofibril repair.…”
Section: Discussionmentioning
confidence: 99%